The implementation of a balanced scorecard perspective to SMEs performance - Rosita Mei Damayanti; Eva Yuniarti Utami; Diah Pramesti; Dama Yuninata; Rohmawan Adi Pratama; Versiandika Yudha Pratama (Sebelas Maret Business Review, 2023)
This paper aims to investigate the impact of implementing the balanced scorecard perspective on the performance of micro, small, and medium enterprises (SMEs) in the F&B, fashion, craft, and services sectors in Central Java and Yogyakarta. A total of 170 respondents participated in the online and offline survey, and after removing incomplete data, 164 observations were analysed. The balanced scorecard perspective, consisting of financial, customer, internal process, and organizational learning and growth perspectives, was used as an independent variable, while performance was used as a dependent variable. The research also included digitalization and control variables such as gender, education sector, and size of SMEs. The results suggest that customer satisfaction and loyalty significantly affect SMEs’ performance and profitability. Testing the implementation of the balanced scorecard across various sectors, the research finds that its effects are not significant in sectors such as fashion, craft, services, and others sectors. The research recommends emphasizing the importance of maintaining a positive relationship with customers to increase revenue and profitability. Though financial and learning variables did not have significant effects, SMEs should still consider them as they may lead to customer satisfaction.